The Use of Promoting Questions in Play Activities with the Playworld Approach in Kindergarten - widya Sari, winda; Yus, Anita; Husna Handayani, Peny; Afria Damayanti, Nina (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
The current challenge for teachers is how learning in Kindergarten (TK) through play can help children acquire an understanding of a concept. This study aims to explain the use of promoting questions, identify the types of promoting questions that can help children understand a concept, and explain the process by which promoting questions help children understand the concept of